The Role of Digital Marketing in Enhancing the Growth of Small and Medium Enterprises in Port Harcourt Metropolis, Rivers State, Nigeria - Ebiye GEORGE; Tamaranebi OGE; Oke Christopher JOHN (ABUAD Journal of the Humanities-AGIDIGBO)
Digital marketing has emerged as a transformative force for small and medium enterprises (SMEs), especially in developing economies where traditional marketing channels are limited or ineffective. This study examines the relationship between digital marketing and SMEs’ growth in Port Harcourt Metropolis, Rivers State, Nigeria. A mixed-methods research design was adopted, involving surveys with 150 SME owners and interviews with 10 stakeholders. Regression analysis and thematic evaluation were used to explore the extent of digital marketing adoption, its impact on business growth, and challenges to implementation. Findings show that while digital marketing improves customer engagement and brand awareness, adoption is limited by infrastructure deficits, low digital literacy, and affordability concerns. Policy recommendations are provided to enhance digital adoption and build SME competitiveness.